2021
DOI: 10.47197/retos.v43i0.87875
|View full text |Cite
|
Sign up to set email alerts
|

Utilidad de la virtualidad en las prácticas profesionales de fisioterapia en el contexto de la pandemia COVID-19 (Usefulness of virtuality in physiotherapy professional practices in the context of the COVID – 19 pandemic)

Abstract: Introducción: La formación profesional en salud enfrenta grandes desafíos desde que el distanciamiento social se volviera una de las estrategias para el control de la pandemia por COVID-19. La educación en fisioterapia tiene un componente práctico que requiere contacto con los pacientes y mediante el cual los estudiantes adquieren competencias profesionales. Esta modalidad presencial de aprendizaje ha tenido que ser reemplazada por nuevas estrategias pedagógicas, como la atención mediada por tecnologías… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
0
4
0
4
Order By: Relevance
“…These competencies address much more than the implementation of theoretical knowledge, since they also incorporate the development of other transversal competencies, such as respectful treatment of the user and the achievement of effective communication. In addition, the use of digital technologies for the development of telemedicine could generate added value in common non-pandemic contexts, where students require innovative techniques that ensure their training quality and contribute to the achievement of competencies 16 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These competencies address much more than the implementation of theoretical knowledge, since they also incorporate the development of other transversal competencies, such as respectful treatment of the user and the achievement of effective communication. In addition, the use of digital technologies for the development of telemedicine could generate added value in common non-pandemic contexts, where students require innovative techniques that ensure their training quality and contribute to the achievement of competencies 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, telemedicine prevents the execution of anthropometric measurements to users (weight, height, and others), restricting the realization of an integrated and accurate nutritional diagnosis, as well as limiting the development of other practical skills in students, which require face-to-face contact with users. In this sense, some authors have reported difficulties associated with distance learning activities, such as the impossibility of developing motor skills, the need for internet connection, decreased interaction between teacher and students, increased levels of distraction, among others 12,16 . Therefore, it has been mentioned that it is necessary to complement online teaching and learning activities with face-to-face interventions with users, for the development of other practical skills in students 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…La Federación Internacional de Triatlón generó algunas consideraciones para la realización del entrenamiento indoor (Sellés & Carrasco, 2020), todas estas estrategias con el fin de evitar la pérdida de forma deportiva, la cual fue la mayor preocupación tanto para entrenadores como deportistas (Yasmid et al, 2020;Alarcón & Hall, 2021;Seguí et al, 2021); además, de prevenir la deserción de la práctica (Martínez et al, 2021;Carvajal et al, 2021). La adaptación del entrenamiento a las nuevas condiciones fue compleja, los atletas debieron acomodar de una u otra forma sus hogares en escenarios deportivos y trabajar con los materiales que tenían a la mano con el fin de continuar con su proceso de entrenamiento.…”
Section: Población Y Muestraunclassified